MENINGKATKAN KEMAMPUAN SISWA PADA PEMBELAJARAN OPERASI HITUNG PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT MELALUI MEDIA KARTU BILANGAN PADA KELAS V DI SDN 24 TEMMALEBBA KEC. BARA KOTA PALOPO - Juli Pratama Saputri (Pedagogik Journal of Islamic Elementary School, 2018)
The study aims to 1) Knowing whether the use of number card media can inprove students’ ability on the subject matter of counting and reducting analysis of 5th grade integers at SDN 24 Temmalebba. 2) To know the improvement of students’ ability on material count arithmetic operation and reduction of integer through media of number card in class V/A at SDN 24 Temmalebba. This research is a classroom action research conducted in class V/A. Data collection tecnique which in conducted observation method, documentation, interview and test. Data analysis conducted in this research is decriptive analysis that is data reduction, data presentation and conclusion. The results of this research indicate that: 1) By using the number card media, the students’ ability on the learning of the counting operation of the sum and reduction of the integers of grade students can increase. 2) Improvement of students’ ability test result on learning of sum and integer counting operation every cycle has increased, it can be seen from the average of student’s learning result that is less categorized prasiklus less that average value equal to 52 or klasikal equal to 14,29%, in te first cycle is categorized enough from the average value of 62,3 or by classically 42,86%and on cycle 2 is categorized very well from the average value of 83 or by classical 88,57%. Therefore the number card media need to be used as a reference by the teacher in the activity of calculating the operation of counting and the reduction of integers in primary school..